1987
DOI: 10.1259/0007-1285-60-711-245
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of radiation dose to the thyroid using positron emission tomography

Abstract: Measurements of the functioning volume of thyroid tissue have been made in 22 patients undergoing radioiodine therapy for thyrotoxicosis, using a prototype multiwire proportional counter positron camera. Tomographic images were produced of the distribution of 124I in the thyroid. Functioning volumes were found to be in the range 21-79 cm3 with volume errors of the order of +/- 4% to +/- 14%. Radioiodine uptake varied from 28% to 98%. Using a value of 6 days for the effective half-life of radioiodine in hyperac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Some groups have even proposed a role for positron emission tomography in dose calculation, which would clearly add considerably to costs. [2627] Our study also suggests that a fixed dose approach works as well and could lead to greater patient convenience while at the same time reducing medical costs. [11] A large study by Damle et al ., in 633 patients with diffuse toxic goiter also suggested that first dose success of a fixed 185 MBq dose radioiodine is high when assessed over a period of 1 year.…”
Section: Discussionmentioning
confidence: 60%
“…Some groups have even proposed a role for positron emission tomography in dose calculation, which would clearly add considerably to costs. [2627] Our study also suggests that a fixed dose approach works as well and could lead to greater patient convenience while at the same time reducing medical costs. [11] A large study by Damle et al ., in 633 patients with diffuse toxic goiter also suggested that first dose success of a fixed 185 MBq dose radioiodine is high when assessed over a period of 1 year.…”
Section: Discussionmentioning
confidence: 60%
“…Whilst PET is still an expensive technique there will be five centres in operation in the UK in the next 2 years and there should be further possibilities to expand on a broader front (Ott, 1987) by sharing radiopharmaceutical facilities on a regional basis. The unique, quantitative, functional information provided by PET makes it an exciting addition to the imaging tools available to the oncologist to help improve both diagnosis and therapy.…”
Section: Discussionmentioning
confidence: 99%
“…PET imaging can be considered for treatment planning but ideally requires the use of a radioisotope from the same ele-ment as that used for treatment (for example I-124 for I-131 or Y-86 for Y-90). I-124 has been applied to dosimetric assessments as early as 1986 [95] particularly for the dosimetry of radioiodine therapy of benign thyroid diseases [96,97]. In 1991 the use of I-124 was proposed for quantifying in vivo tumor concentration and biodistribution for radioimmunotherapy [98][99][100].…”
Section: Pet-based Dosimetrymentioning
confidence: 99%